Social protection and the International Monetary Fund: promise versus performance - Alexandros Kentikelenis; Thomas Stubbs (BMC, 2024)
Abstract Background Countries in the Global South are currently facing momentous economic and social challenges, including major debt service problems. As in previous periods of global financial instability, a growing number of countries have turned to the International Monetary Fund (IMF) for financial assistance. The organization has a long track-record of advocating for extensive fiscal consolidation-commonly known as 'austerity'-for its borrowers. However, in recent years, the IMF has announced major initiatives for ensuring that its loans support social spending, thus aiding countries in meeting their development targets and the Sustainable Development Goals. To assess this track record, we collected spending data on 21 loans signed in the 2020-2022 period, including from all their periodic reviews up to August 2023. Results We find that austerity measures remain a core part of the organization's mandated policies for its borrowers: 15 of the 21 countries studied here experience a decrease in fiscal space over the course of their IMF programs. Against this fiscal backdrop, social spending floors have failed to live up to their promise. There is no streamlined definition of these floors, thus rendering their application haphazard and inconsistent. But even on their own terms, these floors lack ambition: they often do not foresee trajectories of meaningful social spending increases over time, and, when they do, many of these gains are eaten up by soaring inflation. In addition, a third of social spending floors are not implemented-a much lower implementation rate from that for austerity conditions, which the IMF prioritizes. In several instances, where floors are implemented, they are not meaningfully exceeded, thus-in practice-acting as social spending ceilings. Conclusions The IMF's lending programs are still heavily focused on austerity, and its strategy on social spending has not represented the sea-change that the organization advertised. At best, social spending floors act as damage control for the painful budget cuts: they are instruments of social amelioration, underpinned by principles of targeted assistance for highly disadvantaged groups. Alternative approaches rooted in principles of universalism can be employed to build up durable and resilient social protection systems.